2023
DOI: 10.3390/antiox12020456
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Amaranth (Amaranthus hybridus chlorostachys) Supplemented with Enzyme Blend on Egg Quality, Serum Biochemistry and Antioxidant Status in Laying Hens

Abstract: A feeding trial was performed to assess the effects of dietary raw amaranth (Amaranthus hybridus chlorostachys) grain (RAG), with or without an enzyme blend, on the productive performance, blood biochemistry, and antioxidant status in laying hens. The trial was conducted following a completely randomized design by factorial method, including five levels of RAG (0, 10, 20, 30, and 40%, respectively) and two levels of enzyme blend (0 −E and 0.025 +E %). A total of 960 White Leghorn (Hy-line W-36) laying hens (56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
3
11
0
Order By: Relevance
“…Popiela et al [ 18 ] did not observe any negative effect on some blood antioxidant characteristics and liver enzymes by feeding amaranth in laying hens, which was consistent with the results of the present study. Furthermore, Janmohammadi et al [ 1 ] showed that feeding raw amaranth grain to laying hens can lead to a decrease in blood cholesterol and maintain the antioxidant status of the blood in a normal and stable state, in agreement with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Popiela et al [ 18 ] did not observe any negative effect on some blood antioxidant characteristics and liver enzymes by feeding amaranth in laying hens, which was consistent with the results of the present study. Furthermore, Janmohammadi et al [ 1 ] showed that feeding raw amaranth grain to laying hens can lead to a decrease in blood cholesterol and maintain the antioxidant status of the blood in a normal and stable state, in agreement with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…By increasing the recycling of bile secretion, a decrease in cholesterol occurs. Considering the amount of bile secretion in laying hens, which is about one milliliter per kilogram of body weight per hour, if the recycling of bile secretion can be increased, decreased cholesterol and triglyceride content can be expected [ 1 , 28 ]. St-Onge et al [ 60 ] hypothesized that feeding amaranth grain and its active compounds stimulates the binding of cholesterol with bile acids and prevents the formation of micelles, while also increasing the fermentation effect on the production of fatty acids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, concerted efforts have been made to further explore the incorporation of grain amaranth into avian diets as a strategy to replace traditional feed resources. A review of the literature revealed maintenance or improvement in performance indices (Popiela et al, 2013, hypocholesterolemic effects (Alizadeh-Ghamsari et al, 2021), improved antioxidant status and atherogenic indices (Hosseintabar-Ghasemabad et al, 2022), improved animal health and improved production of healthier products (Popiela et al, 2013, Janmohammadi et al, 2023 when amaranth was incorporated into poultry diets, either raw or processed, or with other additives. Furthermore, when different amaranth species were evaluated, records revealed significant variability in terms of essential nutrients (Szabóová et al, 2020), phytochemical and antinutrient levels (Mlakar et al, 2009), animal feed consumption and weight gain (Waldroup et al, 1985, Pond et al, 1991, Ravindran et al, 1996.…”
Section: Introductionmentioning
confidence: 99%